Unusual presentation of Sturge-Weber syndrome: Progressive megalencephaly with bilateral cutaneous and cortical involvement - Mittal, Kundan (Medknow Publications & Media Pvt Ltd, 2014)
The Sturge Weber syndrome is characterized by developmental delay, seizures in infancy, unilateral cutaneous lesions with ipsilateral leptomeningeal enhancement. We report an unusual presentation of Sturge Weber syndrome with bilateral port wine nevus on the trunk and face along with bilateral cortical involvement in a developmentally normal child with progressive megalencephaly.